Volumetric and Refractive Properties of [Difurylmethane + (2-Propanol or 2-Butanol)] Binary Mixtures at 298.15 K - Nyanzi, Steven; Mokate, Ogorogile; A.A. Ddamba, Wilfred (Asian Journal of Chemistry, 2010)
Densities (ρ) and refractive indices (nD), for [difurylmethane + (2-propanol or 2-butanol)] binary systems have been measured over the entire concentration range at 298.15 K and atmospheric pressure. The ρ-data were correlated by established literature model in order to check the relationship accounting for the dependence of density on composition. Calculated excess molar volumes (VmE) and excess molar refraction (ΔR), have been fitted to the Redlich-Kister polynomial to estimate the binary coefficients (Ak) and the standard deviations (σfit) of the fits. The excess partial molar volumes (ViE) of the components of each binary system were examined to provide insight into the variation with composition, of the intermolecular interactions present. The results have been discussed in terms of specific intermolecular interactions and structural effects.